Case study: what supports students to improve their grades?. (3rd May 2016) - Sieminski, Sandy; Messenger, Julie; Murphy, Sam
Abstract: This case study considers students who achieved 'borderline' (40–45%) grades in their first assignment on a module, but went on to markedly improve their grades over the course of the module. The students were studying nursing and social work at the UK Open University, and they were all sponsored by employers. Semi-structured telephone interviews were used to explore the experiences of the students, including the way in which they reacted to assessment feedback and how this contributed to their learning and development. Other themes that emerged from the study include the emotions experienced by the students, sometimes challenging their self-confidence and evoking feelings associated with emotional vulnerability, and the tendency for students to initially approach assessment independently, but later to create and take advantage of opportunities for social learning. The role of the tutor in helping students to prepare for assessment appears to be significant, as does the fact that students are sponsored by their employers, which provides an additional incentive to complete the module.